Hans Scharoun. Philharmonie, Berlin 1956-1963. - (:unkn) unknown (Wasmuth, 2013)
Der fünfte Band der O´Neil Ford Monograph-Reihe, herausgegeben vom Center for American Architecture and Design (CAAD) und dem O´Neil Ford Chair in Architecture an der University of Texas at Austin analysiert in englischer Sprache ein wichtiges Bauwerk moderner Architektur an Hand von zahlreichen Fotos, Originalskizzen und Plänen.

Rising with its golden roof from the self-inflicted ashes of World War II, right at the center of the remains of Hitler´s megalomaniac World Capital Germania, the new concert hall for the Berlin Philharmonic Orchestra has become the symbol of another Germany; a newly democratized nation that sought to reshape itself with the help of cultural experiences. Today, the Philharmonie is the nucleus of Berlin´s Kulturforum with five museums, two concert venues and the state library, West Berlin´s response during the Cold War to the Museum Island on the east of Berlin. Hans Scharoun´s design for the Philharmonie is without precedent. It became the paradigm for numerous concert halls all over the world, but none has ever come close to the Philharmonie´s conceptual, compositional, constructional, social and synesthetic experiential integrity.
Keywords: Bebauung; Konzerthaus; Architektur; Wettbewerb; Planungsprozess; Zielkonflikt